Shaping Translation: A View from Terminology Research - Antia, Bassey; Budin, Gerhard; Picht, Heribert; Rogers, Margaret; Schmitz, Klaus-Dirk; Wright, Sue (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThis article discusses translation-oriented terminology over a time frame that is more or less congruent with META’s life span. Against the backdrop of the place of terminology in shaping professional issues in translation, we initially describe some stages in the process by which terminology has acquired institutional identity in translator training programmes and constituted its knowledge base. We then suggest a framework that seeks to show how theory construction in terminology has contributed to a better understanding of technical texts and their translation. A final section similarly illustrates how this overarching theoretical scheme has driven, or is at least consistent with, products and methods in the translation sector of the so-called language industries.